Closing the implementation gap: applying a behavioral science integration in the current WHO and CDC infection prevention policies - Sabbah, Ahmad; Albalwi, Fatmah; Al-Omrani, Awad; Albalawi, Hanan (The Journal of Infection in Developing Countries, 2026)
Introduction: Despite decades of technical guidance, healthcare-associated infections (HAIs) remain a global challenge. Although the current infection prevention and control (IPC) guidelines, produced by the WHO and the CDC, provide robust procedural recommendations, they do not fully address the behavioral determinants of compliance. Objectives: This study evaluates both the WHO and CDC IPC guidelines for areas in which the Social Cognitive Theory (SCT) constructs are integrated to strengthen behavioral strategies. Methodology: The study used qualitative content analysis on 17 IPC documents (published during 2010-2023). Using a deductive coding framework based on the SCT, documents were systematically analyzed using NVivo 12. Comparative assessments examined temporal trends and differences between agencies. Results: Environmental influences were most consistently represented (15–25%), while self-efficacy (5–15%) and observational learning (4–11%) were underemphasized. The WHO guidelines demonstrated greater progress, with self-efficacy content rising from 5% (2010) to 15% (2023). The CDC guidelines placed stronger emphasis on reinforcement (12%) but showed limited growth in self-efficacy and observational learning. Integration of multiple constructs within a single recommendation occurred in only 28% of all reviewed documents. Conclusions: Digital health policies currently underapply behavioral science concepts. Future revisions should adopt SCT constructs rigorously, demand more leadership modeling, and leverage technology for feedback. This behavioral approach could bridge policy and practice for a more effective IPC program.